Postoperative Hip Center Position Associated With the Range of Internal Rotation and Extension During Gait in Hip Dysplasia Patients After Total Hip Arthroplasty - Hu, Yi; Zou, Diyang; Sun, Qi; Jiang, Mengda; Li, Huiwu; Tsai, Tsung-Yuan; Zhang, Jingwei (Frontiers in Bioengineering and Biotechnology, 2022)
Background: Total hip arthroplasty (THA) for hip dysplasia patients is sometimes complex and compromises pathomorphological changes in these patients. However, it remains unclear whether it is preoperative deformities or postoperative structures, or anatomic changes during THA that have the most remarkable correlation with the hip dynamic function during gait. The purpose of this study was to investigate this relationship and propose insight for surgical reconstruction strategy in patients with developmental dysplasia of the hip. Methods: Twenty-one unilateral hip dysplasia patients received CT scans for the creation of 3D hip models before surgery and at the last follow-up. Acetabular and femoral orientations, hip center position, and femoral length were measured before and after THA. Hip kinematics of the operated side during gait was quantified using a dual fluoroscopic imaging technique. Pearson correlation and multiple linear regression were performed to evaluate the relationship between hip maximum range of motion in six directions and demographics characters and above hip anatomic parameters before and after THA and their changes in surgery. Results: Pearson correlation analysis found significant correlations with gait range of motion mainly in postoperative structures, including postoperative hip center position, acetabulum and combined anteversion. Further multiple linear regression indicated that a laterally placed hip center was significantly correlated with increased internal rotation (R2=0.25, P=0.021), which together with increased postoperative acetabulum anteversion explained 45% of external rotation decreasing (P=0.004). A proximally placed hip center was correlated with less extension (R2=0.30, P=0.010). No significant demographic characters, or preoperative deformities, or surgical changes were included into other multiple regression models. Conclusions: Strong correlations between postoperative structures, especially hip center positions, and gait range of motion in unilateral hip dysplasia patients after THA were found. It indicated that postoperative prosthesis structures, particularly hip center position, had significant impact on hip gait motion range and should be treated with particular caution in surgery.